Genome-wide assessments reveal extremely high levels of polymorphism of two active families of mouse endogenous retroviral elements. - Ying Zhang; Irina A Maksakova; Liane Gagnier; Louie N van de Lagemaat; Dixie L Mager (PLoS Genetics, 2008)
Endogenous retroviral elements (ERVs) in mice are significant genomic mutagens, causing approximately 10% of all reported spontaneous germ line mutations in laboratory strains. The majority of these mutations are due to insertions of two high copy ERV families, the IAP and ETn/MusD elements. This significant level of ongoing retrotranspositional activity suggests that inbred mice are highly variable in content of these two ERV groups. However, no comprehensive genome-wide studies have been performed to assess their level of polymorphism. Here we compared three test strains, for which sufficient genomic sequence is available, to each other and to the reference C57BL/6J genome and detected very high levels of insertional polymorphism for both ERV families, with an estimated false discovery rate of only 0.4%. Specifically, we found that at least 60% of IAP and 25% of ETn/MusD elements detected in any strain are absent in one or more of the other three strains. The polymorphic nature of a set of 40 ETn/MusD elements found within gene introns was confirmed using genomic PCR on DNA from a panel of mouse strains. For some cases, we detected gene-splicing abnormalities involving the ERV and obtained additional evidence for decreased gene expression in strains carrying the insertion. In total, we identified nearly 700 polymorphic IAP or ETn/MusD ERVs or solitary LTRs that reside in gene introns, providing potential candidates that may contribute to gene expression differences among strains. These extreme levels of polymorphism suggest that ERV insertions play a significant role in genetic drift of mouse lines.